Management of recurrent urinary tract infections in adults. Issue 4 (April 2020) - Lodhia, Siya; Sharaf, Ala'a; Foley, Charlotte
Abstract: Many women will experience one or more urinary tract infection (UTI) during their life. The most unfortunate will have many. Men presenting with infections, and women with recurrent episodes, require further investigation. A diagnosis of a UTI is often based on a typical spectrum of symptoms, with confirmatory urine cultures lagging a few days behind. Unfortunately, symptoms of a UTI may not be typical, and other conditions can manifest similarly. Treatment of UTI with antibiotics is usually required, but there is increasing awareness of the need for antimicrobial stewardship to avoid the misuse and overuse of antibiotics, even as patients are increasingly reluctant to take them. Recurrent UTI can cause significant morbidity and disruption to daily activities yet investigations rarely demonstrate a reversible cause. There are a host of different antibiotic and non-antibiotic interventions that aim to lower the risk of further infections. However, these are not reliably effective, bring side effects of their own and are often proposed to this desperate population of patients on the back of weak evidence of efficacy.